Hybrid lipid-polymer nanoplatform: A systematic review for targeted colorectal cancer therapy. (15th March 2023) - Dave, Richa; Patel, Rashmin; Patel, Mrunali
Graphical abstract: Abstract: Colorectal cancer (CRC) is among the most rampant diseases globally and still has a high fatality and relapse rate despite the significant developments in conventional treatment modalities. In the realm of effective cancer treatments, nanotechnology-based drug delivery systems have attracted great interest. The most researched drug delivery system for successful cancer therapy is liposomes because of their unique qualities, such as biocompatibility, improved entrapment efficiency, and scalability as well as cost-effective process. While on the contrary, polymeric nanoparticles possess good stability, controlled release, and the capability for several chemical alterations. However, lipid peroxidation, burst release, restricted surface changes, and polymer toxicity limit their applications. Thus, lipid-polymer hybrid nanoparticles (LPHNPs) have been identified as promising nanosystems with respect to a number of biomedical applications. These particles are a prospective delivery system made up of combinatorial properties of liposomes and polymeric nanoparticles. A deeper understanding of LPHNPs types, synthesis aspects with their controllable parameters, release mechanisms, and surface functionalization are all elements of the current review. This review article emphasizes the significant uses of LPHNPs relating to the delivery of drugs and their targeting as well as the obstacles hampering their clinical translation with the potential for utilizing these nanoplatforms to treat colorectal cancer.